2023
DOI: 10.1111/sms.14450
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of active commuting to and from school to device‐measured physical activity levels in young people: A systematic review and meta‐analysis

Pablo Campos‐Garzón,
Javier Sevil‐Serrano,
Antonio García‐Hermoso
et al.

Abstract: ObjectiveTo analyze the contribution of active commuting to and from school (ACS) to device‐measured light physical activity (LPA) and moderate‐to‐vigorous physical activity (MVPA) levels in young people aged 6 to 18 years old, as well as, in both trip directions (i.e., home‐school, school‐home).MethodsThis systematic review was conducted according to the PRISMA statement, and five different databases were used for the systematic search (PubMed, Web of Science, SPORTdiscuss, Cochrane Library, and National Tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 70 publications
0
11
0
Order By: Relevance
“…Three reviews [ 29 , 32 , 34 ] investigated interventions concerning “active school transport” and “active commuting to and from school”. In reviews of [ 29 , 34 ], accelerometers were used to measure PA in all included studies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Three reviews [ 29 , 32 , 34 ] investigated interventions concerning “active school transport” and “active commuting to and from school”. In reviews of [ 29 , 34 ], accelerometers were used to measure PA in all included studies.…”
Section: Resultsmentioning
confidence: 99%
“…Three reviews [ 29 , 32 , 34 ] investigated interventions concerning “active school transport” and “active commuting to and from school”. In reviews of [ 29 , 34 ], accelerometers were used to measure PA in all included studies. Larouche et al reported that 13 interventions resulted in a statistically significant increase in active school transport whereas eight reported no changes at all, four included studies recorded inconsistent results and five did not record inferential statistics.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 17 Whole-day school uniforms, for which items are often also segregated by gender, could similarly influence students’ physical activity behavior. These uniforms are typically worn for longer periods than PE attire and during times when young people accrue a greater portion of their daily physical activity (e.g., during recess, 33 school travel 34 , 35 ). Observational research studies have found that some girls perceive their whole-day uniforms as a barrier to break-time play 36 , 37 and school active travel.…”
Section: Introductionmentioning
confidence: 99%